2013
DOI: 10.1002/app.40161
|View full text |Cite
|
Sign up to set email alerts
|

Solvent diffusion in silica/poly[styrene‐co‐(acrylic acid)] core‐shell microspheres by pulsed field gradient NMR techniques

Abstract: Polymer‐coated SiO2 particles are prepared by precipitation of poly[styrene‐co‐(acrylic acid)] on SiO2 microspheres through an improved phase inversion method. The diffusion resistance of the polymer membrane was considered to be the critical reason for producing tailor‐made polyethylene by catalysts supported on these polymer‐coated particles. This paper employs pulsed field gradient NMR (PFG‐NMR) to distinguish diffusion of n‐hexane in different regimes, i.e., in the space between each particle, the pores in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(36 reference statements)
0
5
0
Order By: Relevance
“…A few examples are presented in Table 3. lignin and switch grass as reinforcement; polymeric methylene diphenyl diisocyanate (PMDI) as compatibilizer [256] filler: acidolysis lignin and alkali enzymatic lignin [257] WAXD and SAXS investigations revealed that presence of the AL does not influence the crystal and supermolecular characteristics of the PHB [258] poly(3hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) lignin was obtained from sugar cane bagasse; lignin content up to 80% [112] starch reactive filler; lignin stabilizes the residual starch structure [259] mixed matrix: cellulose and starch; lignin filler (1-5 wt%); hybrid green composite films with excellent mechanical properties in dry and wet states, and good thermal stability and high gas barrier [260] matrix: glycerol-plasticized corn starch (GCS)adipic acid modified starch microparticles (AASM) [261] PA tall oil based polyamide [283] polybutylene adipate-ωterephtalate applications: non-food packaging or other short-lived applications (agriculture, sport) [262] PLA PEG added as plasticizer [263] three silane coupling agents: 3-aminopropyltrieethoxysilane, γ-glycidoxypropyl-trimethoxy-silane, and gmethylacryloxy-propyltrimethoxy-silane [264] composites exhibited a six-fold increase of elongation at break and a simultaneous improvement in their tensile strength and Young's modulus [265] comparative study using PP or PLA as matrix, and cellulose, lignin or wood flour as filler [266] matural rubber (NR) NR/soda lignin and NR/thiolignin composites [267] improvement of main mechanical properties [268] comparative study on natural rubber (NR) and styrene butadiene rubber (SBR) matrices; lignin filler -forming agglomerates [269] epoxidized natural rubber [270] homogeneous dispersion of filler and the strong interfacial adhesion significantly enhanced the thermal stability and mechanical properties of nanocomposites [187]…”
Section: Lignin Reinforced Bioplastic Compositesmentioning
confidence: 99%
“…A few examples are presented in Table 3. lignin and switch grass as reinforcement; polymeric methylene diphenyl diisocyanate (PMDI) as compatibilizer [256] filler: acidolysis lignin and alkali enzymatic lignin [257] WAXD and SAXS investigations revealed that presence of the AL does not influence the crystal and supermolecular characteristics of the PHB [258] poly(3hydroxybutyrate-co-3-hydroxyvalerate) (PHBV) lignin was obtained from sugar cane bagasse; lignin content up to 80% [112] starch reactive filler; lignin stabilizes the residual starch structure [259] mixed matrix: cellulose and starch; lignin filler (1-5 wt%); hybrid green composite films with excellent mechanical properties in dry and wet states, and good thermal stability and high gas barrier [260] matrix: glycerol-plasticized corn starch (GCS)adipic acid modified starch microparticles (AASM) [261] PA tall oil based polyamide [283] polybutylene adipate-ωterephtalate applications: non-food packaging or other short-lived applications (agriculture, sport) [262] PLA PEG added as plasticizer [263] three silane coupling agents: 3-aminopropyltrieethoxysilane, γ-glycidoxypropyl-trimethoxy-silane, and gmethylacryloxy-propyltrimethoxy-silane [264] composites exhibited a six-fold increase of elongation at break and a simultaneous improvement in their tensile strength and Young's modulus [265] comparative study using PP or PLA as matrix, and cellulose, lignin or wood flour as filler [266] matural rubber (NR) NR/soda lignin and NR/thiolignin composites [267] improvement of main mechanical properties [268] comparative study on natural rubber (NR) and styrene butadiene rubber (SBR) matrices; lignin filler -forming agglomerates [269] epoxidized natural rubber [270] homogeneous dispersion of filler and the strong interfacial adhesion significantly enhanced the thermal stability and mechanical properties of nanocomposites [187]…”
Section: Lignin Reinforced Bioplastic Compositesmentioning
confidence: 99%
“…The most popular applications involving NMR diffusion methods concern themselves with directly estimating a molecular weight (MW) frequently with the help of model compounds, as indicated in Fig. .…”
Section: D‐values and Molecular Weightsmentioning
confidence: 99%
“…Spin–lattice ( T 1 ) relaxation experiments were performed and evaluated for reactant methanol in coked catalyst samples. Signal recovery curves and fittings are shown in Figure b.…”
Section: Methodsmentioning
confidence: 99%